Makna dan Konsep Arsitektur Tradisional Bali dan Aplikasinya dalam Arsitektur Masa Kini - Susanta, I Nyoman (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment); Vol 4 No 2 (2017): October 2017DO - 10.24843/JRS.2017.v04.i02.p08, 2017)
This is a study of principles and meanings encompassing the traditional Balinese Architecture. Its conduct is underlined by a deep concern that Balinese practices in the built form will not survive, as many determining circumstaces have inevitably changed overtime. This article aims at providing an understanding in regard to non-physical aspects which would be crucial when changes and transformations of the Balinese architectural tradition are seen necessary. It proposes continuous modification and repetition related practice as a strategy to uphold meanings, concepts, and values contained within this tropical architecture. This research was carried out using qualitative research approach. Data collection was done by conducting a field survey and literature study. Discussions and analyses presented within have been enriched by author's practical experiences in the field.   Keywords : meaning, principle, traditional architecture, modifikation, transformation